(untitled) (Training and Practice : Journal of Educational Sciences, 2008)
Nowadays Norway is a popular land to settle for immigrants from all over the world. This situation requires taking special measures on the part of the Norwegian state. The main aim of the state is that the immigrants find their feet in the Norwegian society as fast and smoothly as possible. An essential instrument to this is the learning of Norwegian in a short time; the state provides the furthering of this by a law, by the Introduksjonsloven. This law includes the regulation of programmes for adult immigrants in the interest of their easier integration such as organization of courses for Norwegian language and social studies. For the immigrants children is this aim to be achieved by attending educational institutions; the most determinative are nursery school and primary school in order to get to Norwegian speaking surroundings as early as possible. In addition also the participation of immigrants young people in the higher-level education is very important. All these are supported by the Norwegian state: such Norwegian as a second language can be chosen as an alternative of Norwegian as mother tongue in the primary school, and many courses and fields of study are offered at the universities in Norway. An other aim of the Norwegian policy is the supporting of mother tongue learning and preservation. From the 1980s the mother tongue teaching was characteristic of the schools in Norway, what for our days has been changed. Nowadays „mother tongue teacher” are employing in the schools who help the immigrant children to understand the material of the lessons; but this isn’t real language teaching. The Norwegian state primarily doesn’t consider mother tongue teaching a school-task, in the case of so many different nationality groups (immigrants) it couldn’t be realizable.